2024
DOI: 10.1007/s00382-024-07180-8
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning with autoencoders and LSTM for ENSO forecasting

Chibuike Chiedozie Ibebuchi,
Michael B. Richman

Abstract: El Niño Southern Oscillation (ENSO) is the prominent recurrent climatic pattern in the tropical Pacific Ocean with global impacts on regional climates. This study utilizes deep learning to predict the Niño 3.4 index by encoding non-linear sea surface temperature patterns in the tropical Pacific using an autoencoder neural network. The resulting encoded patterns identify crucial centers of action in the Pacific that serve as predictors of the ENSO mode. These patterns are utilized as predictors for forecasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
0
0
Order By: Relevance
“…Unlike models that may struggle with the temporal patterns in a time series, FFNN, and LSTM can capture and leverage the underlying dependencies present in the past six months' data to make accurate predictions for the upcoming six months. Recently, consistent with our results, several other studies have successfully applied neural networks to forecast ENSO with promising accuracy at several lead times, and at times outperforming dynamical models [11,17,[45][46][47][48][49][50][51][52]. For example, the study by Ham et al [47] applied deep learning with a convolutional neural network (CNN) to forecast the Niño 3.4 index in up to 17 months lead time, achieving a correlation of at least 0.5.…”
Section: Comparison Of Various Machine Learning Models In Enso Foreca...supporting
confidence: 88%
See 1 more Smart Citation
“…Unlike models that may struggle with the temporal patterns in a time series, FFNN, and LSTM can capture and leverage the underlying dependencies present in the past six months' data to make accurate predictions for the upcoming six months. Recently, consistent with our results, several other studies have successfully applied neural networks to forecast ENSO with promising accuracy at several lead times, and at times outperforming dynamical models [11,17,[45][46][47][48][49][50][51][52]. For example, the study by Ham et al [47] applied deep learning with a convolutional neural network (CNN) to forecast the Niño 3.4 index in up to 17 months lead time, achieving a correlation of at least 0.5.…”
Section: Comparison Of Various Machine Learning Models In Enso Foreca...supporting
confidence: 88%
“…Hu et al [45] applied deep residual convolutional neural network and heterogeneous transfer learning to achieve 83.3% accuracy for forecasting EI Niño type in 12-month lead time. Similar impressive results were also achieved by other studies applying deep learning for ENSO forecasting [11,50].…”
Section: Comparison Of Various Machine Learning Models In Enso Foreca...supporting
confidence: 85%
“…In prior work, we have demonstrated that the Nonhomogeneous Hidden Markov Model (NHMM) applied to gridded, monthly SST data can objectively identify 5 ENSO flavors (whose spatial patterns and time of occurrence are similar to those of the 5 types of events typically identified), their temporal dynamics 24 , and their implications for global precipitation 23 . Further its 1-18 month ahead prediction skill for the benchmark Niño 3.4 index is comparable to that of other popular machine learning models 19,[25][26][27] . Given its interpretability and relative accuracy, we use it to explore how the temporal dynamics of ENSO may have changed relative to changing global temperature.…”
Section: Introductionsupporting
confidence: 56%
“…It is well recognized that using a single ENSO index does not adequately represent the spatiotemporal dynamics or allow for an effective long-term ENSO prediction model 14,1516,17 . In addition to deterministic physics-based models, a variety of machine learning methods [18][19][20][21][22][23] have been advanced to simulate the dynamics of ENSO diversity. In prior work, we have demonstrated that the Nonhomogeneous Hidden Markov Model (NHMM) applied to gridded, monthly SST data can objectively identify 5 ENSO flavors (whose spatial patterns and time of occurrence are similar to those of the 5 types of events typically identified), their temporal dynamics 24 , and their implications for global precipitation 23 .…”
Section: Introductionmentioning
confidence: 99%